2020
DOI: 10.1038/s41598-020-64495-2
|View full text |Cite
|
Sign up to set email alerts
|

Infarct in new territory after endovascular stroke treatment: A diffusion-weighted imaging study

Abstract: Data on infarcts in new territory (INT) in patients undergoing endovascular stroke treatment for acute large-vessel occlusions are sparse. Aim of this study was to assess the prevalence, risk factors, and clinical relevance of INT. For this purpose, all patients in a single-center prospective registry who underwent endovascular stroke treatment and received pre- and post-interventional diffusion-weighted imaging were included (N = 259). Using an established scoring system, INT were classified according to size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 16 publications
3
18
2
Order By: Relevance
“…The use of FD-CTP post-thrombectomy is another possible application and the next frontier where FD-CTP could add significant value. In cases of incomplete thrombectomy with residual occlusion—for example, the decision whether to perform rescue maneuvers (eg, with distal stent retrievers24 25 or administration of a thrombolytic drug26 27) or to stop, is currently open to discussion. Intraprocedural magnetic resonance may also aid in such real-time treatment decision-making,28 although FD-CT is considerably simpler from a workflow standpoint.…”
Section: Discussionmentioning
confidence: 99%
“…The use of FD-CTP post-thrombectomy is another possible application and the next frontier where FD-CTP could add significant value. In cases of incomplete thrombectomy with residual occlusion—for example, the decision whether to perform rescue maneuvers (eg, with distal stent retrievers24 25 or administration of a thrombolytic drug26 27) or to stop, is currently open to discussion. Intraprocedural magnetic resonance may also aid in such real-time treatment decision-making,28 although FD-CT is considerably simpler from a workflow standpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Further research could investigate whether PE have an effect on NIHSS scores stratified by symptoms, or with further neurological assessment scores that represent more subtle cognitive changes. Accordingly, Kaesmacher et al showed recently that infarcts larger than 2 cm distal to the occlusion in initially not the hypoperfused territory and new territories are associated with poor outcome [22]. Further studies are warranted to investigate the impact of interventional techniques and devices with regard to thrombus characteristics on the occurrence of PE after MT and their influence on outcome [16,23].…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, pretreatment with intravenous thrombolysis again failed to show an association with rate of INT. 3 At this time, the association of pretreatment intravenous thrombolysis prior to mechanical thrombectomy and rates of ENT remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…3 Large INT (>20 mm) has been shown to be relatively rare with a rate of 5%. 3 The rate of ENT is dependent on a variety of factors including choice of endovascular device, 4 incorporation of balloon guided catheters, 5,6 and method of procedural sedation. 7 Trans-circulation ENT is a rare entity and optimal management is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation